Photophysical Properties of Lumazine in Micellar Media - ACHARYA, SEEMA; VERMA, SARASWATI (Asian Journal of Chemistry, 2010)
The electronic spectral studies include the effect of different micellar heteromicroenvironment on the fluorescence and absorption spectral behaviour of lumazine. It is a medicinally and analytically important biomolecule. The dual nature of surfactant micelle is responsible for the occurrence of surface activity, solubilization and micellization. The increase in fluorescence intensity on addition of surfactant can be attributed to the increase in quantum efficiency. The solubilization phenomenon has also been confirmed by quantitative calculations like quantum yield, molar extinction coefficient (log ε) and Stokes’ shift values and fluorescence coefficient. The fluorescence properties as well as the theoretically calculated spectral data have been used to characterize the microenvironment of the micelles in terms of their micropolarity, probe solubilization site and critical micelle concentration.